2015
DOI: 10.1177/0960327115591377
|View full text |Cite
|
Sign up to set email alerts
|

Changes in developmental body weight as a function of toluene exposure

Abstract: Inhalant abuse is a globally prevalent health issue with particular concerns about substance-abusing pregnant women. In both animal models and clinical case reports of toluene exposure, the primary physiological outcome measure of prenatal inhalant exposure is low birth weight (BW). However, the effect of prenatal toluene exposure on animal BW varies widely in the literature. To clarify this effect and investigate possible design moderators of pup BW, a systematic review and meta-analytic techniques w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…47 The lack of studies using females is particularly concerning because a weight impairment and any associated loss of adiposity 11 during adolescence can cause disruptions to pubertal and metabolic processes due to the endocrinological activity of adipose tissue. 57 Furthermore, as shown by Callan et al, exposure to toluene during pregnancy can impair developmental body weight, 52 and inhalant abuse is most prevalent in females during childbearing years. 2,3 Thus, inhalant abuse in females has the potential to affect not only the individual but also her offspring.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…47 The lack of studies using females is particularly concerning because a weight impairment and any associated loss of adiposity 11 during adolescence can cause disruptions to pubertal and metabolic processes due to the endocrinological activity of adipose tissue. 57 Furthermore, as shown by Callan et al, exposure to toluene during pregnancy can impair developmental body weight, 52 and inhalant abuse is most prevalent in females during childbearing years. 2,3 Thus, inhalant abuse in females has the potential to affect not only the individual but also her offspring.…”
Section: Discussionmentioning
confidence: 97%
“…Some findings are consistent with the literature; for example, toluene exposure has been previously associated with weight gain in mice. 52 It would also be expected that toluene would have a larger effect during adolescence, when growth is accelerating, as opposed to adulthood when growth (particularly height) is more stable. However, data are not consistently available across all subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the authors of the prior study used an industrial exposure paradigm (persistent low concentrations of toluene), which may require third trimester exposure to impair memory function. Indeed, prior work has demonstrated that the deleterious effects of toluene exposure are dependent on “dose”, which in inhalation models is a function of concentration and frequency and duration of exposure, with shorter, higher-concentration exposures producing the most profound effects (Jarosz et al, 2008, Callan et al, 2015). …”
Section: Discussionmentioning
confidence: 99%